Swift Remedy Pharmaceutical Management System for Clinic Mediviron Seapark - Chandransangran, Yashela; Nureize Arbaiy (Applied Information Technology And Computer Science, 2024)
The pharmacy department in hospitals and health facilities provides comprehensive pharmacological care to patients. It oversees sales, drug inventory, and patient information. However, during busy times, overcrowding becomes a problem, resulting in longer wait times and discomfort for patients. To address this issue, an automated pharmaceutical management system called Swift Remedy was developed. Swift Remedy automates various procedures involved in pharmaceutical management, improving workflow efficiency and reducing crowds. It offers new features such as virtual waiting times, mail-order pharmacies, drug inventory management, and medical record monitoring. The creation of Swift Remedy involved object-oriented analysis and an incremental process methodology, utilizing the Visual Studio Code IDE. Swift Remedy is an advanced automated system that has the potential to enhance the efficacy and effectiveness of pharmaceutical care, empowering users to better manage their pharmaceutical activities.